Resistance spikes of NiO/ZnO heterostructures in magnetic field - Sun, Yu-Ze; Qiu, Li-Peng; Gao, Shi-Long; Cao, Shi-Ze; Wang, Shuai-Jie; Han, Wen-Peng; Zhang, Jun; Long, Yun-Ze (Frontiers in Physics, 2025)
NiO/ZnO semiconductor heterostructures were fabricated via electrospinning to investigate their resistance behavior under varying magnetic fields. The resistance of the heterostructures was measured at different temperatures and in magnetic fields of varying strength and direction. Resistance spikes of 1.3%, 5.2%, and 10.7% were observed at 300 K, 290 K, and 280 K, respectively. These resistance variations were found to be influenced by both the magnetic field magnitude and direction, as well as light illumination. The observed phenomena are attributed to the interaction between the heterojunction and the magnetic field, alongside changes in spin electron orientation. This study demonstrates the potential of combining heterostructures and magnetic fields to modulate resistance, offering promising applications for optoelectronic and magnetoelectronic devices.